EVALUATING THE DEBT-GROWTH NEXUS IN ECOWAS: AN INTEGRATIVE FRAMEWORK OF THE BURDEN OF DEBT SERVICING - Ahmed Oluwatobi Adekunle (Gusau Journal of Accounting and Finance)
This study investigates the impact of external debt, external debt servicing, employment, and other macroeconomic variables on economic growth within the ECOWAS sub-region, spanning the period from 2005 to 2023. Utilizing panel data from 15 ECOWAS countries, the analysis employs dynamic panel data models to explore the relationships between these variables. The results suggest that external debt negatively impacts GDP growth, while external debt servicing further exacerbates this negative effect. Conversely, employment levels and foreign direct investment (FDI) show positive associations with economic growth, highlighting their importance for long-term development. Additionally, the study finds that the interaction between external debt and debt servicing has a significant influence on growth, emphasizing the need for effective debt management strategies. These findings offer valuable policy implications for ECOWAS nations, advocating for sustainable debt practices, increased job creation, and enhanced investment policies to foster economic stability and growth in the region.